Antiproliferative effect of Pterogyne nitens on melanoma cells - Regasini, L. O. [UNESP]; Lopes,, A. A. [UNESP]; Silva, D. H.S. [UNESP]; Furlan, Maysa [UNESP]; Young, M. C.M.; Maria, D. A.; Barreiro,, E. J.; Bolzani, Vanderlan da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
As part of our program of bioprospecting for novel antitumor drug prototypes, twenty extracts and fractions obtained from Pterogyne nitens Tul. (Fabaceae, Caesalpinioideae) were screened for antiproliferative activity against B16F10 murine melanoma cells, by the MTT colorimetric assay. The strongest activity was found in EtOAc fractions from the flowers (IC50 = 0.35 µg/mL), fruits (IC50 = 0.34 µg/mL), leaves (IC50 = 0.33 µg/mL) and stems (IC50 = 0.29 µg/mL). Analysis by TLC and HPLC-DAD showed the presence of guanidine alkaloids, flavones and flavonols in the bioactive samples. Additionally, a phytochemical study of the EtOAc fraction of the stems afforded quercetin (1) and isoquercitrin (2), two flavonols with antiproliferative activity previously described in the literature. On the basis of these results, it can be concluded that P. nitens inhibits the growth of melanoma cells in vitro. Further investigations will be needed to assess the usefulness of the samples under study for the treatment of neoplasms and to characterize other bioactive compounds. Keywords: antiproliferative; Pterogyne nitens; Caesalpinioideae; melanoma; flavonoids; Fabaceae.
Keywords: Ciências Farmacêuticas; Farmácia; Farmacologia; Toxicologia; Botânica médica; Plantas medicinais; Atenção Farmacêutica; Assistência farmacêutica; Indústria Farmacêutica.; antiproliferative; Pterogyne nitens; Caesalpinioideae; melanoma; flavonoids; Fabaceae.; Melanona